Introductory notes on planetary science the solar system, exoplanets and planet formation - Salyk, Colette; Lewis, Kevin W. (IOP Publishing, 2020)
Planets come in many different sizes, and with many different compositions, orbiting our Sun and countless other stars. Understanding their properties and interactions requires an understanding of a diverse set of sub-fields, including orbital and atmospheric dynamics, geology, geophysics, and chemistry. This textbook provides a physics-based tour of introductory planetary science concepts for undergraduate students majoring in astronomy, planetary science, or related fields. It shows how principles and equations learned in introductory physics classes can be applied to study many aspects of planets, including dynamics, surfaces, interiors, and atmospheres. It also includes chapters on the discovery and characterization of extrasolar planets, and the physics of planet formation
Keywords: Solar system - the Sun & planets; SCIENCE / Astronomy; Planetary science; Planets